2019
DOI: 10.1089/mdr.2018.0418
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Colistin and Meropenem Resistance Determinants in a Stenotrophomonas Strain Isolated from Sewage Water

Abstract: Development of antibiotic resistance can be achieved either by mutation or by acquiring a resistance gene from foreign sources, with some resistance genes likely originating in microbial populations to counteract antibiotics present in natural ecosystems. In this study, we describe the first report of a strain of nonclinical multidrugresistant Stenotrophomonas sp. strain G4 with high-level resistance to colistin and meropenem, phylogenetically distinct from well-studied multiple drug-resistant species of Steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ newly reported in Raoultella spp. 24 was also identified and appears to be present in Stenotrophomonas spp.. As a confirmation of this hypothesis, this latter has been recently described in Stenotrophomonas strain from sewage water 30 . Interestingly, whilst MCR-8 has only been reported in less than five studies to date, we identified 22 MCR-8 in already sequenced genomes of Klebsiella and Raoultella spp.. All these newly described MCR variants are real true witnesses of our results which predict putative 5'265 MCR-like sequences that could emerged soon in common pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 70%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ newly reported in Raoultella spp. 24 was also identified and appears to be present in Stenotrophomonas spp.. As a confirmation of this hypothesis, this latter has been recently described in Stenotrophomonas strain from sewage water 30 . Interestingly, whilst MCR-8 has only been reported in less than five studies to date, we identified 22 MCR-8 in already sequenced genomes of Klebsiella and Raoultella spp.. All these newly described MCR variants are real true witnesses of our results which predict putative 5'265 MCR-like sequences that could emerged soon in common pathogenic bacteria.…”
Section: Discussionsupporting
confidence: 70%
“…15 was also identified and appears to be present in Stenotrophomonas spp. As a confirmation of this hypothesis, this latter has been recently described in Stenotrophomonas strain from sewage water 34 . Interestingly, whilst MCR-8 has only been reported in less than five studies to date, we identified 22 MCR-8 in already sequenced genomes of Klebsiella and Raoultella spp.…”
Section: Discussionsupporting
confidence: 66%
“…It has recently been reported that the aquatic bacteria of the genus Shewanella are a reservoir/progenitor for mcr -4 encoding gene 47 . MCR-5 and MCR-8 were described from the same Stenotrophomonas strain isolated from sewage water in China 34 . Overall, urban wastewater treatment plants are one of the most common reservoir and source of antibiotic resistance genes (ARGs) against various antibiotic classes (ÎČ-lactams, aminoglycosides, quinolones, tetracyclines, sulfonamides, macrolides) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Restrict treatment choices are feasible for the therapy of infections related to S. maltophilia isolates as a result of its instinctive resistance to various antibiotics owning to many kinds of ÎČ-lactamase or aminoglycosides, especially it is resistant to certain carbapenem and colistin antibiotics (25,26). In view of a systematic review and meta-analysis of non-randomized researches, trimethoprim-sulfamethoxazole manifested commensurate outcomes on rehabilitation of S. maltophilia infection to fluoroquinolones that is considered to be the most effective antibiotics for S. maltophilia (27).…”
Section: Discussionmentioning
confidence: 99%